Eksistensi CV. Satampang Baniah Di Kota Padang Tahun 1985-2020 - Willa Desislawaty; Erniwati Erniwati (Jurusan Sejarah FIS UNP, 2022)
Abstract This article discusses the development of the Satampang Baniah art studio to become CV Satampang Baniah in Padang City in 1985-2020. The problem raised is how the development of the Satampang Baniah studio to become CV Satampang Baniah in Padang City in 1985-2020. The purpose of this study is to explain the development of the Satampang Baniah studio to become CV Satampang Baniah in Padang City in 1985-2020. This study uses historical research methods with sereval stages, the first stage is heuristic seeking and gathering information, the second stege is source criticism, the third stage is interpretation and analysis, and the last stage is historiography. The results showed that the Satampang Baniah studio was founded by Sulastri Andras studio on August 17, 1985 which at time was under the auspices of the Padang SMKI school. In 2005 Sulastri Andras created a legal entity for Satampang Baniah studio so that in 2005 Satampang Baniah studio became CV Satampang Baniah and Sulastri Andras gave the leadership of the studio to her son Marya Danche. This studio from 1985-2020 experienced development in aspects of dance movements, the clothes used, and the number of members of the studio. The performances that initially only filled the arts at the school level and then filled the events at weddings developed into wedding organizer and event organizer, and participated in international art events. The apprearance of the West Sumatra level, nationally, and participated in international art events. The appearance of the studio that always develops according to the times and often wins Minangkabau art competitions, because CV Satampang Baniah is always consistent in presenting Minangkabau arts. The activities of the studio that are increasingly crowded and the various activities that are followed have caused this studio to be able to provide job opportunities to its members with the number of studio members increasing from 25 people in 1985 to 85 people in 2020. Keywords: Development, Art Studio, Art